Anomalous thermal expansion, negative linear compressibility, and high-pressure phase transition in : Neutron inelastic scattering and lattice dynamics studies - Gupta, MK; Singh, B; Mittal, R; Zbiri, M; Cairns, AB; Goodwin, AL; Schober, H; Chaplot, SL (American Physical Society, 2017)
We present temperature-dependent inelastic-neutron-scattering measurements, accompanied by ab initio calculations of the phonon spectra and elastic properties as a function of pressure to quantitatively explain an unusual combination of negative thermal expansion and negative linear compressibility behavior of ZnAu2(CN)4. The mechanism of the negative thermal expansion is identified in terms of specific anharmonic phonon modes that involve bending of the -Zn-NC-Au-CN-Zn- linkage. The soft phonon at the L point at the Brillouin zone boundary quantitatively relates to the high-pressure phase transition at about 2 GPa. The ambient pressure structure is also found to be close to an elastic instability that leads to a weakly first-order transition.